IFSOLAR: the Innovative IFSULDEMINAS Program for the Acquisition of Solar Photovoltaic Plants - Leonardo Silva Manso; Pedro Henrique Mendonça dos Santos (Journal of Sustainability Perspectives, 2023)
IFSOLAR is the project for the bidding, acquisition and installation of photovoltaic plants for the production of solar energy at IFSULDEMINAS, used by public institutions throughout Brazil, and involves SDG 7, 8, 9, 11, 12 and 13. Acquisition of photovoltaic solar plants conducted by IFSULDEMINAS are considered the largest ever carried out in Brazil, with a significant impact on the national energy matrix. The project began in 2016, with the bidding, acquisition and installation of photovoltaic panels on the campuses of 15 Federal Institutes in the country, with a capacity of 5,470 MWp. In 2018, 94 federal agencies participated or adhered to the new tender, moving BRL 220 million, with a capacity of 56 MWp. By the end of 2019, Brazil had approximately 2,100 MWp of distributed generation, and with just the last bid, IFSULDEMINAS contributed to the expansion of 2.7% of the total installed capacity in the country. The performance of IFSULDEMINAS in these innovative bidding processes led to the cost of bidding being reduced by 9% in the final value, for RDC 1/2016, and 41% for RDC 3/2018, reducing the cost for public coffers at BRL 162 million. The IFSOLAR project helped transform IFSULDEMINAS into a reference in the bidding, generation and research of photovoltaic solar energy in the public sector in Brazil.